2009
DOI: 10.1007/s11270-009-0295-2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Abundance of Particle-Phase Organic Pollutants in an Urban/Industrial Atmosphere

Abstract: Polycyclic aromatic hydrocarbons (PAHs); their derivatives nitro, and methyl-PAHs; n-alkanes; and organic acids were investigated in the aerosol samples collected during two field campaigns conducted at three sampling stations in an industrialized city in southern Italy. The main sources affecting the atmosphere and its toxicity were investigated by means of the diagnostic ratios of: specific particulate-phase PAHs, marker compounds among nitro-PAHs, alkanes, and acids, the dominant wind direction, daily and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…All these results were in good agreement with previous studies performed on similar sites and season (summer) (e.g. Albinet et al, 2007aAlbinet et al, , 2008bBamford and Baker, 2003;Di Filippo et al, 2009;Kojima et al, 2010;Liu et al, 2006;Schnelle-Kreis et al, 2001).…”
Section: Particulate Npah and Opah Concentration Levelssupporting
confidence: 93%
“…All these results were in good agreement with previous studies performed on similar sites and season (summer) (e.g. Albinet et al, 2007aAlbinet et al, , 2008bBamford and Baker, 2003;Di Filippo et al, 2009;Kojima et al, 2010;Liu et al, 2006;Schnelle-Kreis et al, 2001).…”
Section: Particulate Npah and Opah Concentration Levelssupporting
confidence: 93%
“…The concentration means for Melpitz are comparable with amounts that have been published earlier (e.g. Di Filippo et al 2010;Harrison and Yin 2010;Cincinelli et al 2004;Guo et al 2003;Kubatova et al 2002).…”
Section: N-alkanessupporting
confidence: 87%
“…Besides the similar sources to PAHs, NPAHs and OPAHs can also be formed from PAHs by photo-chemical oxidation in atmosphere with NO x , O 3 and OH (Bamford and Baker, 2003;Wang et al, 2007;Kojima et al, 2010), and OPAHs from biological transformation in soil with white rot fungi (Lundstedt et al, 2007;Haritash and Kaushik, 2009), respectively. Previous studies mainly focused on the pollution levels of SPAHs in the atmospheric and soil environment (Vincenti et al, 1996;Niederer, 1998;Lundstedt et al, 2007;Di Filippo et al, 2010). Our recent study demonstrated that WWTP effluent contributed 62e93% PAHs and SPAHs (dissolved and absorbed phase) of the total input to the receiving rivers (Qiao et al).…”
Section: Introductionmentioning
confidence: 98%